Status of Hawksbill Turtle and Green Turtle in Negeri Sembilan, Malaysia - Sarahaizad Mohd Salleh; Shahrul Anuar Mohd Sah (Tropical Life Sciences Research, 2024)
This paper highlighted the annual distribution, seasonality and reproduction status of two species of sea turtles in Negeri Sembilan, Peninsular Malaysia between January 2016 and July 2020 (55 months). These data were officially provided by the Department of Fisheries Malaysia (Negeri Sembilan’s state), as a part of a conservation effort made by them to protect the endangered species, as the turtle’s population residing in Negeri Sembilan is one of the smallest in Malaysia. Current status shows that the hawksbill turtles, Eretmochelys Imbricata population in Negeri Sembilan is in stable decline with an average of <30 nests per year, and an average of <10 nests per year for the green turtle, Chelonia mydas. The overall sum was 122 nests collected for both species from 2016–2020. This paper updated the status of the hawksbill and green turtle after 30 years from the first study recorded by Mortimer et al. in 1993.